Sensitivity improvement of optical-fiber temperature sensor with solid cladding material based on multimode interference. (23rd February 2015) - Fukano, Hideki; Kushida, Yohei; Taue, Shuji
Abstract: We have developed a simple, high-sensitivity optical-fiber temperature sensor based on multimode interference (MMI). The fabricated MMI structure comprises three segmented fibers: a single-mode fiber (SMF); a large-core multimode fiber (MMF), whose outer surface is coated with a temperature-sensitive material; and another SMF. Fluoroacrylate and silicone rubber are tested as temperature-sensitive cladding materials. The silicone rubber coating exhibits a large shift in interference wavelength with temperature, producing a very fine temperature resolution as low as 0.01 °C.